Cyberweapons: Leveling the International Playing Field. - Rustici, Ross M. (Parameters: U.S. Army War College)
The article discusses cyberweapons, with particular focus given to their potential to harm the U.S. and methods the U.S. can use to protect itself. The importance of deterrence is emphasized, and the social and psychological effects of successful online attacks is commented on. Discussion of appropriate responses to attacks is also offered.